(untitled) (Research, Society and Development, 2020)
The present work aims to evaluate the hydrodynamics of a pulsed packed extractor, with an internal diameter of 0.026m and a length of 1.0m, using the liquid butanol-water system. Thus, the basic parameters obtained for the hydrodynamic study of the extraction column in question as dispersed phase, slip velocity, characteristic velocity and flooding point. The methodology used in the work consisted of determining the holdup fraction of the dispersed phase, obtained through tests of simultaneous interruptions in the column feedings. The effects of frequency pulsation, dispersed phase flow rate and continuous phase flow rate investigated in the analysis of these parameters. New empirical correlations derived from the predictions of the parameters studied obtained in terms of operating variables and physical properties of the liquid system involved. The average absolute value of the relative error (AARE) was always below 5.6%. Good agreement between calculated and experimental results observed for all investigated operating conditions.